PERUBAHAN STRUKTUR EKONOMI DAN KESEMPATAN KERJA SERTA KUALITAS SUMBERDAYA MANUSIA DI INDONESIA - KETUT KARIYASA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2006)
The result of Assessment on “Changes of Economic and Employment Structure as wellas Quality of Human Resource in Indonesia” showed that in 1995 – 2001 periodseconomic (GNP) structure in Indonesia has been changed from S-I-A (Services-Industry-Agriculture) pattern to I-S-A pattern. Meanwhile, during the same period employmentstructure was remain stable, namely A-S-I pattern. The unbalanced changes betweeneconomic and employment structures were predicted to be the factors causing laborproductivity and society welfare in agricultural sector were declining. In agriculturalsector itself the absorption of labor force was dominated by food crops sub sector. Therewas a quality improvement in human resource. However, the problem is governmentcapability to create employment was not sufficient to provide job opportunity forimproved human resource.